MANAJEMEN LAYANAN KHUSUS KAFETARIA SEKOLAH DENGAN SISTEM FOODCOURT - Fitri Nurtikasari; Ali Imron; Mustiningsih Mustiningsih; Fitri Nurtikasari; Ali Imron (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: This study aims to describe; (1) planning special services for school cafeterias with afood court system; (2) organizing special school cafeteria services with a food courtsystem; (3) implementation of special school cafeteria services with a food courtsystem; (4) supervision of special school cafeteria services with a food court system.This research uses a qualitative approach to the type of case study. The location ofthis research is at SMK PGRI 2 Kediri. Data collection techniques using observation,interview and documentation techniques. This study uses key informants from theChairperson of the Grida Food Court. The results of this study are; (1) planningincludes, objectives, parties involved, cafeteria model, food and beverage menusand prices, cafeteria operational costs, memorandum of agreement; (2) organizingincludes the cafeteria organizational structure and its duties and responsibilities; (3)implementation includes operational hours, types of services, food and beverageproduction processes, provision of food and beverages, provision of facilities andinfrastructure; (4) includes supervision, internal and external supervision